Prognostic Importance of Ki-67 in Breast Cancer and Its Relationship with Other Prognostic Factors - Kanyılmaz, Gül (Eur J Breast Health, 2019)
OBJECTIVE: The clinical feature of breast cancer is very heterogeneous because of the variable prognostic factors impact its behaviour. The aim of study is to find the prognostic importance of Ki-67 and to analyse the correlation between Ki-67 index and the other conventional prognostic factors in breast cancer patients. MATERIALS AND METHODS: Between 2010 and 2017, patients with invasive ductal carcinoma who received radiotherapy after surgery were included in study. A single pathologist re-defined of all cases retrospectively. Ki-67 were established three categories based on Ki-67 levels: low (<10%), intermediate (10–25%) and high (>25%). RESULTS: A total of 258 patients were included. 46 of 258 (18%) patients were in low, 82 of 258 (32%) patients were in intermediate and 130 of 258 (50%) patients were in high Ki-67 group. There were no correlations between menopausal status, age, and Ki-67 level. Low-pT stages tended to have low Ki-67 expression (p=0.07). Low-pN stages correlated with low Ki-67 values (p=0.007). Patients with ECE (+) were prone to have higher Ki-67 values (p=0.02). The significant correlation was seen between Ki-67 and tumour grading (p=<0.0001). Patients with LVI (+) had higher Ki-67 expression (p=0.007). Luminal A tumours were correlated with low Ki-67 group (p=<0.0001). Ki-67 values had significant effect on DFS (p=0.03) but not OS (p=0.09). CONCLUSION: This study showed that high Ki-67 expression is associated with higher pT-stage, higher pN-stage, higher grade, ER/PR negativity, HER2/neu positivity, ECE and LVI positivity. The prognostic impact of Ki-67 was only demonstrated for DFS.